Voices of the Korean Minority in Postwar Japan : histories against the grain - Ropers, Erik (Routledge studies in the modern history of Asia, 2018)
"Shedding new light on how the histories of zainichi Koreans have been written, consumed, and discussed, this book addresses the roots of postwar debates concerning the wartime experiences of Koreans in Japan. Providing an overview of the complicated historiography, it explores the experiences of Koreans located at Ground Zero in Hiroshima and Nagasaki, as well as the history and processes that coerced Korean women into military prostitution. These debates and controversies continue to attract attention regionally and globally and, as this book demonstrates, they are deeply embedded in ideas dating back decades earlier. By tracing the roots of these debates in historical writings from local history groups to zainichi and Japanese scholars, we may see how written histories have been used for particular social, political, or cultural purposes and how they have lent support to certain interpretations and memories of past events across the political spectrum. Interdisciplinary at its core, Voices of the Korean Minority in Postwar Japan will appeal to audiences including those interested in modern Japanese and Korean history, historiography and methodology, and memory studies"-- |c Provided by publisher.